Top Brand Award Ranking Analysis Using Social Network Analysis on Coffee Shops on Twitter Social Media - herdiany, alvioneta dinda; Asih, Tri Sri Noor (Universitas Negeri Semarang, 2025)
The coffee shop business is one of the very busy businesses. A number of coffee shop brands in Indonesia have begun to emerge. One of the fastest growing fast food coffee chains in Indonesia is Kopi Kenangan. Top Brand is conducting a poll in 2023 to determine the preferred level of consumption for local coffee. According to the findings of the Top Brand Award 2023 survey, Kenangan coffee with a value of 39.70% occupies the first position in the online and offline food and beverage category, while Janji Jiwa coffee is in second place with a value of 39.50%. Janji Jiwa Coffee is one of the fast-growing franchise companies in Indonesia. This study uses the Social Network Analysis (SNA) method to find out which coffee shop brands have higher activity by comparing network properties on Twitter social media. The source of this research data was obtained from the results of crawling data on Twitter social media with the keywords